Morphology of the vertebral centra in dolphins from the southwestern South Atlantic: A 3D morphometric approach and functional implications - Marchesi, María Constanza; Boy, Claudia Clementina; Dans, Silvana Laura; Mora, Matias Sebastian; Gonzalez-Jose, Rolando (Marine Mammal Science)
In dolphins, centrum shape is one of the features that allows determination of stable and flexible regions in the vertebral column. The Commerson's (Cephalorhynchus commersonii; n = 37), Peale's (Lagenorhynchus australis; n = 24), dusky (Lagenorhynchus obscurus; n = 29), and hourglass dolphins (Lagenorhynchus cruciger; n = 10) are closely related species inhabiting the Southern Hemisphere that have diverse prey and habitat preferences. We applied 3D geometric morphometrics to describe differences in centrum shape along the vertebral columns of these species, and hypothesize how these differences may affect swimming. On each column, we chose a maximum of eight vertebrae and digitized 18 landmarks on each centrum with a Microscribe G2X. We explored shape differences amongst regions employing principal components analyses and computing Mahalanobis distances. We describe differences in centrum shape in relation to functional regions and among species; and analyze shape changes in relation to particular biomechanical requirements. The species studied here may be partially sympatric in the Southern Hemisphere, but they have important differences in foraging ecology and habitat preferences that could be related to differences in centrum shape along the vertebral column. Fil: Marchesi, María Constanza. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Boy, Claudia Clementina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Dans, Silvana Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Mora, Matias Sebastian. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del ...